Determinan yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah - Purwasih, Ratih; Yulianita, Anna; Sari, Rela (SAFE-Network, 2023)
The government is required to present quality financial reports as a form of accountability to the public. This study aims to analyze the effects of the implementation of government accounting standards, the utilization of institutional-level financial application system, the administration of state property and the implementation of reconciliation on the quality of government financial reports. The population in this study were the employees of finance and state property within the Directorate General of Public Health, Ministry of Health of the Republic of Indonesia, totaling 56 peoples. The sampling technique is the census method, in which all members of the population are sampled. The data used in this research is primary data with data collection techniques through questionnaires. The data analysis method used in this research is SEM-PLS by using SmartPLS. The results of this study indicate that the implementation of government accounting standards, the utilization of institutional-level financial application system, the administration of state property and the implementation of reconciliation each have a positive and significant effect on the quality of government financial report. This shows that increasing the implementation of government accounting standards, the utilization of institutional-level financial application system, the administration of state property and the implementation of will have an impact on improving the quality of government financial report.